Pathophysiological Role of Purinergic P2X Receptors in Digestive System Diseases - An, Qimin; Yue, Gengyu; Yang, Xiaoxu; Lou, Jun; Shan, Weixi; Ding, Jianhong; Jin, Zhe; Hu, Yanxia; Du, Qian; Liao, Qiushi; Xie, Rui; Xu, Jingyu (Frontiers in Physiology, 2021)
P2X receptors(P2XRs) are trimeric, non-selective cation channels activated by extracellular ATP and widely distributed in the digestive system. P2XRs have an important role in the physiological function of the digestive system, such as asneurotransmission, ion transports, proliferation and apoptosis, muscle contraction and relaxation. P2XRs can be involved in pain mechanisms both centrally and in the periphery and confirmed the association of P2XRs with visceral pain. In the periphery, ATP can be released as a result of tissue injury, visceral distension, or sympathetic activation and can excite nociceptive primary afferents by acting at homomeric P2X(3)R or heteromeric P2X(2/3)R. Thus, peripheral P2XRs, and homomeric P2X(3) and/or heteromeric P2X(2/3)R in particular, constitute attractive targets for analgesic drugs. Recently studies have shown that P2XRs have made significant advances in inflammation and cancer. P2X7R mediates NLRP3 inflammasome activation, cytokine and chemokine release, T lymphocyte survival and differentiation, transcription factor activation, and cell death. The P2X7R is a potent stimulant of inflammation and immunity and a promoter of cancer cell growth. This makes P2X7R an appealing target for anti-inflammatory and anti-cancer therapy. It is believed that with the further study of P2XRs and its subtypes, P2XRs and its specific antagonists will be expected to be widely used in the treatment of human digestive diseases in the future.